Pengaruh Perlakuan PGV-1, PGV-0 dan Kurkumin terhadap Protein yang Terlibat dalam Siklus Sel Fase G2-M dan Apoptosis pada Sel Kanker Payudara T 47D - MUHAMMAD DA'I; UMAR ANGGARA JENIE; SUPARDJAN AM; EDY MEIYANTO; MASASHI KAWAICHI (Fakultas Farmasi Universitas Pancasila, 2012)
Previous experiments showed that curcumin analogue (PGV-1) inhibited breast cancer cell (T47D) growth at G2-M phase and induced cell apoptosis. This experiment was conducted to investigate the molecular effect of another curcumin analogue, PGV-0 and curcumin on the cell cycle progression and apoptosis as compared to the PGV-1. F lowcytometric method was conducted to analyze the effect of PGV-1 (2,5 µM), PGV-0 (5,0 µM) and curcumin (10,0 µM) on the cell distribution of various phase of T47D cell cycle. Western blot was also conducted to observe the effect of those compounds on proteins that involved in cell cycle (i.e. p21 and Cdc-Z) and apoptosis (Caspase-3/7/9). The results showed that PGV-1, PGV-0 and curcumin induced hyperploidy phenomenon on T47D cell. PGV-1 inhibited the cell cycle specifically on G2-M phase. Molecular observation showed that PGV-1 and PGV-0 were able to increase the expression of p21 protein and the Cdc-2 proteins, whilst curcumin was able to activate the Cdc-2 protein. The compounds have ability to induce apoptosis on T47D cell via Caspase3/7 activation. In conclusion, PGV-1, PGV-0 and curcumin inhibited the T47D cell cycle progression and induced cell apoptosis.